An Analysis of Character Education Values in the ELT Textbook for Junior High School Students - Azura Dwi Prastika Sukma (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Character education is essential in developing students' personalities. In education, students not only gain academic knowledge but also character education, which can be used by students in developing their character. This study investigated character education in the seventh-grade ELT textbooks in the emancipated curriculum. It was expected to have a significant impact on character education development, which is needed in developing ELT textbooks. In addition, English teachers can also implement the character education values in the ELT textbooks. They can select content in the ELT textbooks emphasizing character education, which aligns with character education in the emancipation curriculum. This research analyzed visual artifacts in the form of pictures contained in the ELT textbook. The object of this research was an ELT textbook, "English for Nusantara," for seventh-grade secondary schools, published by the Ministry of Education and Culture in 2022. It was the first book published in the emancipated curriculum. It contains five chapters and 264 pages for 2 semesters. In each chapter, there were visual artifacts that reflected character education. The visual artifacts were used as data in this study and analyzed using the Ministry of Education and Culture's character education framework, which includes having faith, fear of the Almighty God and noble character, global diversity, cooperation, independence, critical thinking, and creativity. Moreover, in collecting data, this research used documentary research (document analysis) by Bowen (2009). The data obtained was analyzed using qualitative content analysis by Ari et al. (2010). The results showed that six categories of character education value were presented in the ELT textbook through 16 pictures. Those characteristics include having faith, fear of the Almighty God and noble character, global diversity, cooperation, independence, critical thinking, and creativity. This textbook is recommended as a learning resource for character education because it aligns with the learning objectives of this current curriculum. This research has limitations. It has character gaps in this book. HFFAG/NC characters appeared more dominantly than others, such as global diversity and critical thinking. They only appeared once. Therefore, teachers and authors must play an active role in overcoming the shortcomings in the ELT textbook. For Future research, they can explore the same topic using a different focus or method. They can investigate character education by focusing on textual material and using. critical discourse analysis (CDA) for the research method.
Keywords: Character Education; ELT Textbook